Peran Masyarakat Dusun Batantangan Pada Masa Revolusi Fisik di Kalimantan Selatan - Prawitasari, Melisa; Nuraida, Lisna; Mansyur, Mansyur (Prabayaksa: Journal of History Education, 2021)
One of the battle headquarters for the struggle at the end of the physical revolution in South Kalimantan that takes place was in Batantangan Hamlet, Batu Bini Village, Padang Batung District. The headquarters, located in Batantangan Hamlet, is a strategic place, also it is in the middle of the dense forest of the Meratus Mountains. This headquarters is also located among other areas of battle so that this place became the gate or entrance to other areas during the physical revolution battle in South Kalimantan. This study aims to find out more about the Batantangan Hamlet as the headquarters of the guerrilla battle at the end of the physical revolution in South Kalimantan and the role of the society in the activities of the guerrilla battle. The method used in this research is the historical method which consists of Heuristics, Criticism, Interpretation and Historiography. The first step is heuristics or collecting data. The data were obtained through three things, first oral sources obtained from the results of interviews done by the researchers with community leaders who experienced the period of physical revolution in Batantangan Hamlet. Second, written sources such as thesis, dissertations, journals, books and the last source is some of objects obtained by researchers during field observations. After the data was collected, the next step is criticism, both internal and external criticism. The next is interpretation and the last stage is historiography or writing of research results. The results showed that the position of Dusun Batantangan as a headquarters for guerilla fighters during the physical revolution was so important and the emotional proximity of the Dusun Batantangan society with fighters that made the society help the fighters in guerella battle